Editorial Comments - Editorial Office (AOSIS, 2002)
South Africa is a multicultural and multilingual countrywith eleven official languages and many more dialects.Persons from each cultural group adhere to uniquevalues, attitudes and beliefs influencing their health.Nurses come from all cultural groups. Rendering culturesensitive and culture congruent care in such diversehealth care settings, poses unique ethical problems,which can only be addressed if the health care workerspossess the required knowledge and skills.